2007
DOI: 10.1021/jf0726583
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Profiling of Native Andean Potato Tubers (Solanum tuberosum L.) Reveals Cultivars with High Levels of β-Carotene, α-Tocopherol, Chlorogenic Acid, and Petanin

Abstract: The antioxidant profile of 23 native Andean potato cultivars has been investigated from a human nutrition perspective. The main carotenoid and tocopherol compounds were studied using high-performance liquid chromatography coupled with a diode array detector (HPLC-DAD) and a fluorescence detector, respectively, whereas polyphenols (including anthocyanins in colored tubers) were identified by means of both HPLC-mass spectrometry and HPLC-DAD. Antioxidant profiling revealed significant genotypic variations as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
6
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(148 citation statements)
references
References 47 publications
11
128
6
3
Order By: Relevance
“…In our earlier experiments (Hamouz et al 2010) we discovered that stress conditions in the cultivation of potatoes, including drought stress, may show an increased content of phenolic compounds. Our observation of increase in CA due to drought stress is supported by the results of André et al (2007) who found in experiments that their responses to drought stress were highly cultivar-specific. The antioxidant contents of the yellow tuber-bearing cultivars (Sipancachi and SS-2613) were weakly affected by the drought y -yellow; w -white; p -purple; r -red.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In our earlier experiments (Hamouz et al 2010) we discovered that stress conditions in the cultivation of potatoes, including drought stress, may show an increased content of phenolic compounds. Our observation of increase in CA due to drought stress is supported by the results of André et al (2007) who found in experiments that their responses to drought stress were highly cultivar-specific. The antioxidant contents of the yellow tuber-bearing cultivars (Sipancachi and SS-2613) were weakly affected by the drought y -yellow; w -white; p -purple; r -red.…”
Section: Resultssupporting
confidence: 88%
“…Also André et al (2007André et al ( , 2009 indicate that the contents of total phenolics and individual phenolic compounds, most of which is represented by chlorogenic acid, were significantly influenced by various factors such as genotype of potato cultivars with yellow, red and purple flesh. Influence of location.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies have placed potato into the perspective of an antioxidant-rich crop. More precisely, potatoes contain phenolic compounds including hydroxycinnamic acids, the predominant being chlorogenic acid (André et al, 2007b, Brown, 2005 and flavonoids, for example www.intechopen.com catechin, epicatechin and anthocyanins. Potato contains low amounts of carotenoids, such as -carotene (Brown, 2005), indicating that potato is not a good source of pro-vitamin A carotenes; more important are the oxygenated carotenoids, the xantophylls, such as neoxanthin, violaxanthin, antheraxanthin, lutein and zeaxanthin (Griffiths et al, 2007).…”
Section: Antioxidants In Potatomentioning
confidence: 99%
“…Antioxidant profiling of native Andean potato tubers revealed higher levels of carotenoids and polyphenolics including chlorogenic acid and the anthocyanin petanin (also known as petunidin-3-(p-coumaroylrutinoside)-5-glucoside), the latter was reported to be exceptionally high in darkpurple-fleshed cultivars (Andre et al, 2007). Genotypic variation was also found to be the predominant factor affecting the contents of phenolics and carotenoids, compared to other parameters such as location and year (Hamouz et al, 2010;Lachman et al, 2009;Reddivari, Hale, & Miller, 2007;Wegener, Jansen, Juergens, & Schuetze, 2009).…”
Section: Introductionmentioning
confidence: 99%